Back Cover: Giant Volume Change and Topological Gaps in Temperature‐ and Pressure‐Induced Phase Transitions: Experimental and Computational Study of ThMo2O8 (Chem. Eur. J. 3/2016). Issue 3 (January 2016) - Xiao, Bin; Kegler, Philip; Gesing, Thorsten M.; Robben, Lars; Blanca‐Romero, Ariadna; Kowalski, Piotr M.; Li, Yan; Klepov, Vladislav; Bosbach, Dirk; Alekseev, Evgeny V.
Abstract : A pressure‐induced phase transition in ThMo2 O8 is followed by a giant decrease in volume and dramatic structural changes. As a result, the less thermodynamically stable HP modification survives and remains kinetically stable after release of the pressure. More information can be found in the Full Paper by E. V. Alekseev et al. onpage 946 ff .